Penanaman Agama Pada Keluarga Muslim Dari Pernikahan Di Bawah Umur - Khotimah, Afifah Khusnul; Al Amin, Muhammad Nur Kholis; Santoso, Fattah S; Shobaruddin, Dudin; Yusri, Nurul (Universitas Cokroaminoto Yogyakarta, 2024)
This sociology of family study seeks to identify parenting patterns and methods of cultivating religion in families where husband and wife marry underage. This research was conducted using qualitative methods in Joho Village, Sukoharjo District, Sukoharjo Regency. The subjects in this research were three families of couples who married underage, while the informants in this research were village officials, parents of children who married early and close relatives. Data collection techniques were carried out by means of observation, interviews and documentation. The data validity technique in this research uses source triangulation and method triangulation. The analysis technique in this research uses interactive analysis from Miles and Huberman. The research results show that the family applies a democratic parenting style. In religious immersion, the methods applied by parents are the example method, the advice method and the habituation method.